Implantação da infraestrutura de saneamento básico em áreas urbanas de ocupação - Albuquerque, Priscila Gomes Pereira de (Universidade Federal de São Carlos, 2021)
The present work was carried out with the residents of Jardim Ipiranga, a district located in the city of Sorocaba, which had its urbanization through the occupation of an area where a farm was located. Broadly aimed to understand and analyze the process of implementing the basic sanitation infrastructure, focusing on water distribution and sewage collection and treatment in the context of the struggle for the right to the city. The research was characterized by a qualitative approach, through a case study and used the interview technique, which took place after approval by the UFSCar ethics committee. This study demonstrated that the urbanization process was implemented in a context of struggles for rights, through the manual labor of the poor inhabitants, who carried out the task of deforestation, self-construction and opening of streets for the installation of sanitation pipes. It was also concluded that the urbanization of the area had the no-institutional and veiled participation of the government and that the process of implementing the basic sanitation infrastructure took place in two stages, until the entire completion of this implementation, the residents used different strategies for access to water and sewage drainage.
Implementation of basic sanitation infrastructure in occupied urban areas
Keywords: Saneamento básico; Direito à cidade; Urbanização; Basic sanitation; Urbanization; Right to the city; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO::CLASSES SOCIAIS E GRUPOS DE INTERESSE; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::INSTALACOES HIDRAULICO-SANITARIAS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ASPECTOS FISICO-AMBIENTAIS DO PLANEJAMENTO URBANO E REGIONAL